Is aid for infrastructure effective? A difference-in-difference-in-differences approach - Julian Donaubauer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2016)
The effects of foreign aid on the endowment of recipient countries with infrastructure have received surprisingly little attention in the empirical literature. This paper addresses this question by performing difference-in-difference-in-differences estimations, with the treatment defined as steep increases in aid for infrastructure since a distinct change in donor behavior in 2005. Mitigating endogeneity concerns in this way, we consistently find aid for infrastructure to be ineffective in improving the recipient countries' endowment with infrastructure. This finding holds not only for an encompassing index of economic infrastructure, but also for sub-indices of infrastructure in transportation, communication, energy, and finance.
Keywords: F35; O18; 330; sector-specific aid; aid effectiveness; infrastructure; difference-in-difference-in-differences